Classification of Tidal Inlets Along the Central West Coast of India. (2015) - Vikas, M.; Reddy, N. Amaranatha; Rao, Subba; Seelam, Jaya Kumar
Abstract: Tidal inlets along the Maharashtra coast on the central west coast of India were classified according to three methods available in the literature. Two classification methods viz., (i) Hydrodynamic classification (Hayes, 1979) and (ii) Classification based on dimensionless parameters (Vu, 2013) used for the classification are compared with the morphological classification of de Vriend et al., (1999). The hydrodynamic classification of Tidal inlets along Maharashtra coast is carried out considering mean annual significant wave height. The classification is also extended considering significant wave heights obtained for South-West monsoon, North-East monsoon and Fair Weather seasons. It has been observed that 74% of the inlets are tide dominated as per morphological classification whereasconsidering annual mean wave heights in Vu (2013) method, 67% of the inlets are wave dominated.